Analisis Kedudukan Pekerja Outsourcing: Kajian Terhadap Putusan MK Nomor 168/PUU-XXI/2023 - Ardelia, Talita Adwa; Hibahtillah, Muhammad Alldo; Imon, Syarah Adilla; Ningrum, Galuh Prima; Damayanti, Ratih; Naelufar, Rizqan; Agung, Muhammad Fariz Nur; Aini, Ailia Nur (Media Hukum Indonesia (MHI), 2024)
The decision of the Constitutional Court No. 168/PUU-XXI/2023 has a significant impact on the regulation of outsourced labor in Indonesia, especially in the protection of workers' rights. The abolition of Article 65 of the Labor Law created a legal vacuum that triggered uncertainty, particularly regarding the types of work that could be outsourced. This decision confirms that outsourcing is only allowed for non-major jobs to protect permanent workers from the risk of replacement. The main challenge lies in government supervision and the drafting of clear implementing regulations. This research emphasizes the importance of supervision, worker rights education, and social dialogue between the government, companies, and trade unions. These measures are expected to improve the protection of outsourced workers, create a fair and sustainable labor system, and support deeper labor reform.